2004
DOI: 10.1074/jbc.m406758200
|View full text |Cite
|
Sign up to set email alerts
|

Hydrolytic Polyketide Shortening by Ayg1p, a Novel Enzyme Involved in Fungal Melanin Biosynthesis

Abstract: The pentaketide 1,3,6,8-tetrahydroxynaphthalene (T4HN) is a key precursor of 1,8-dihydroxynaphthalenemelanin, an important virulence factor in pathogenic fungi, where T4HN is believed to be the direct product of pentaketide synthases. We showed recently the involvement of a novel protein, Ayg1p, in the formation of T4HN from the heptaketide precursor YWA1 in Aspergillus fumigatus. To investigate the mechanism of its enzymatic function, Ayg1p was purified from an Aspergillus oryzae strain that overexpressed the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
83
0

Year Published

2007
2007
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 92 publications
(85 citation statements)
references
References 28 publications
2
83
0
Order By: Relevance
“…This NRPKS is a member of Group III instead of Group II. This classification is consistent with previous biochemical analysis, which showed that synthesis of THN by WA is a result of chain shortening of the heptaketide product YWA1 (44). The well-studied PksA and other NRPKSs that are involved in the synthesis of C4-C9/C2-C11 cyclized aromatic polyketides are clearly separated into Group IV.…”
Section: Resultssupporting
confidence: 75%
“…This NRPKS is a member of Group III instead of Group II. This classification is consistent with previous biochemical analysis, which showed that synthesis of THN by WA is a result of chain shortening of the heptaketide product YWA1 (44). The well-studied PksA and other NRPKSs that are involved in the synthesis of C4-C9/C2-C11 cyclized aromatic polyketides are clearly separated into Group IV.…”
Section: Resultssupporting
confidence: 75%
“…1), which is then enzymatically converted to T4HN, as shown in Fig. 2C (17,40). YWA1 is metabolized to T4HN by a post-PKS polyketide shortening mechanism (17) involving a protein called Ayglp.…”
mentioning
confidence: 99%
“…This reaction occurs upstream of the T4HN reductase step that is required for the synthesis of scytalone. Other compounds made in A. fumigatus include 1, 3, vermelone, and D2HN (6,17). The reductase that converts T4HN to scytalone can be blocked by a specific pathway inhibitor known as tricyclazole (20).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…21 The translational product PKS4 is capable of producing aromatic polyketides using acylCoAs as substrates as reported by Tang et al 21 This PKS4 naturally found in G. fujikuroi is responsible for the biosynthesis of bikaverin (1, Figure 6), a fungal polyketide exhibiting anticancer activity. Mirroring the YWA1 biosynthetic pathway, 25 a proposed mechanism for assembling the aromatic rings involves an aldol condensation reaction between C2 and C7 of the first ring followed by a Claisen condensation between C10 and C1 to form the pentaketide 1, 3, 6, 8-tetrahydroxynaphthalene 26,27 scaffold by the thioesterase/Claisenlike cyclase (TE/CLC) domain in the enzyme which is finished off by a pyrone formation reaction. Subsequently, compound 2 is provided through a dehydration followed by cyclization between C12 and C17.…”
Section: Aromatic Polyketides Biosynthesized Using Pks4mentioning
confidence: 99%